Bacteriophage endolysins: applications for food safety. (February 2016) - Schmelcher, Mathias; Loessner, Martin J
Graphical abstract: Highlights: Endolysins are promising agents for detection and control of foodborne pathogens. Cell wall binding domains can be used for specific detection of bacteria in food. Endolysins can be applied by different strategies along the food production chain. Different approaches can render endolysins active against Gram-negative bacteria. Endolysins support removal of bacterial biofilms from abiotic surfaces. Abstract : Bacteriophage endolysins (peptidoglycan hydrolases) have emerged as a new class of antimicrobial agents useful for controlling bacterial infection or other unwanted contaminations in various fields, particularly in the light of the worldwide increasing frequency of drug-resistant pathogens. This review summarizes and discusses recent developments regarding the use of endolysins for food safety. Besides the use of native and engineered endolysins for controlling bacterial contamination at different points within the food production chain, this also includes the application of high-affinity endolysin-derived cell wall binding domains for rapid detection of pathogenic bacteria. Novel approaches to extend the lytic action of endolysins towards Gram-negative cells will also be highlighted.